The implementation of the minimal intervention dentistry in the undergraduate dental clinical teaching: A retrospective audit / Siti Mariam Ab Ghani ... [et al.] - Ab Ghani, Siti Mariam; Tengku Mohd Ariff, Tengku Fazrina; Ong, Teng Kai; Lim, Tong Wah (Faculty of Dentistry, Universiti Teknologi MARA, 2022)
Objectives: This study aims to assess the prevalence of minimal intervention dentistry (MID) treatment planned during the undergraduate clinical teaching. Materials and Methods: In this retrospective audit, clinical records from 108 dental students were collected and categorized into three cohorts; 2009/2014, 2010/2015, and 2011/2016. The number of direct restorations [amalgam restorations (AR) and composite restorations (CR)], fixed partial dental prostheses [conventional bridges (CB) and resin-bonded-bridges (RBB)] and single tooth indirect restorations (crowns and onlays) prescribed clinically by the undergraduate clinicians were retrieved. Results: Among the three cohorts, a trend was observed in the decrease of AR and the increase of CR prescribed by the dental students. The highest AR (9.6%) was performed by Cohort 2009/2014 and the highest CR (97.7%) was performed by Cohort 2011/2016. For fixed partial dental prostheses, RBB (67.6%) was the main treatment of choice, as compared to CB (32.4%). The cohort 2011/2016 prescribed the highest number of RBB as compared to earlier cohorts. In cases where teeth required cuspal protection, crowns (91.4%) dominated the treatment modality compared to onlays (8.6%). Conclusion: This study showed the dental undergraduates in UiTM endorsed the MID approach as recommended in the contemporary restorative dentistry.